Technical and Economic Analysis of The Use of Heat Pumps in a Public Facility - Wiekiera, Radosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A heat pump uses natural energy from renewable sources such as air, ground or water. The pump, acquiring thermal energy from the environment (75%) and using electricity (25%), supplies it to the heated object. A heat pump-based system consists of a ground heat source (heat is taken from it), a heat pump unit and an upper heat source (heat is transferred to it).
Keywords: air-water heat pump; ground-water heat pump; heat pumps; RES; pompa ciepła powietrze-woda; pompa ciepła grunt-woda; pompa ciepła; OZE